Efecto de una curva rápida de congelamiento profundo de semen porcino utilizando el antioxidante L-carnitina - Caldevilla, Mariana (2018)
Results in fertility and litter size obtained using frozen-thawed porcine semen are very different from those obtained with natural service or artificial insemination of cooled semen. The objective of this study was to evaluate freeze-thawing of porcine semen comparing the\ntraditional slow method to a rapid curve of temperature descent, using two cryoprotectants\n(glycerol and dimethylformamide) in presence of an antioxidant and an energy substrate (Lcarnitine and pyruvate). Nine males of proven fertility (n=9, r=2) were used. Semen was obtained using the gloved-hand technique and was transported to the laboratory at 17 ºC\ndiluted in Androstar®\nplus. Samples were centrifuged at 800 g for 15 minutes and re-diluted\nin: a) 5% DMF, lactose 11%, 20% egg yolk, 0.5 % Equex; b) 3% glycerol, lactose 11%, 20% egg yolk, 0.5 % Equex; c) 5% DMF, lactose 11%, 20% egg yolk, 0.5 % Equex + L-carnitine 50 mM and pyruvate 10 mM and d) 3% glycerol, lactose 11%, 20% egg yolk, 0.5 % Equex +\nL-carnitine 50 mM and pyruvate 10 mM. Samples were frozen in 0.5 ml straws, to a final concentration of 300 x 106 sperm /ml, with either a modified slow curve or a rapid curve of\ntemperature descent. Thawing was carried out at 37 ºC during 1 minute. Cinetic motility\nparameters were evaluated using a CASA system (ISAS v1, Proiser® , Spain). Sperm viability and acrosome status were evaluated using the FITC-PNA/PI stain. Sperm morphology was\nevaluated in a wet mount with formol saline solution using a phase contrast microscope and\nunder oil immersion. Sperm acrosome status and membrane functional integrity were\nevaluated simultaneously by using the Coomassie blue stain (CB) on sperm submitted to the\nhypoosmotic swelling test (HOS). A factorial experimental design, with three factors of two\nlevels each, and using the male as a blocking factor, was applied and Kruskal Wallis was used when data did not show a normal distribution. No significant differences (p> 0.05) were\nobserved between slow or rapid curves, nor between cryoprotectants (DMF and glycerol), nor between presence or absence of L-carnitine and pyruvate for any of the motility, morphology,\nCB/HOS patterns or live acrosome reacted and dead acrosome intact sperm (FITC-PNA/PI)\nevaluated postthaw. However, significant differences (p< 0.05) in live acrosome intact and\ndead acrosome reacted spermatozoa with the FITC-PNA/PI stain were observed between using the slow vs. the rapid curve. Hence, either glycerol or dimethylformamide could be\nused as cryoprotectants and the addition of L-carnitine (50 mM) together with pyruvate (10 mM) to the freezing media did not make a difference to the sperm quality of thawed porcine\nsemen. With regard to the temperature descent curves, a rapid curve that can be performed in just ten minutes can be applied in this species. One of the most important advantages of this method is that it can be carried out in the field and on any pig farm, dispensing with the need\nto move either the semen samples or the stallions, and in addition it does not require costly equipment.